Synthesis and Charaterization of Pd(II) and Pt(II) Complexes with ligands derived from 9,10-Phenanthroquinone Monoxime and Different isomers of Diamino Benzene - Kumar, R.N.; Kumari Chauhan, Nilam; Kumar Mandal, Ganesh (Asian Journal of Chemistry, 2010)
The complexes of bivalent palladium and platinum with bis( 9, 10-phenanthroquinone monoximato) 1,2-diamino benzene [L1]. bis-(9,10-phenanthroquinone momoximato) 1,3-diamino benzene [L2] and bis-(9,10-phenanthroquinone momoximato) 1,4-diamino benzene [L3] have been synthesised and characterized on the basis of elemental analysis, magnetic, susceptibility measurement, infrared and electronic spectra, conductivity measurement and 13C NMR spectra.